Application of Solid-State NMR to Reveal Structural Differences in Cefazolin Sodium Pentahydrate From Different Manufacturing Processes - Tian, Ye; Wang, Wei D.; Zou, Wen-Bo; Qian, Jian-Qin; Hu, Chang-Qin (Frontiers in Chemistry, 2018)
Solid-state Nuclear magnetic resonance, thermogravimetric analysis, X-ray diffraction, and Fourier-transform infrared spectroscopy were combined with theoretical calculation to investigate different crystal packings of α-cefazolin sodium obtained from three different vendors and conformational polymorphism was identified to exist in α-cefazolin sodium. Marginal differences observed among cefazolin sodium pentahydrate 1, 2, and 3 were speculated as being caused by the proportion of conformation 2.